1999
DOI: 10.1038/sj.jhh.1000796
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and management of patients with uncontrolled, severe hypertension: results from a public teaching hospital

Abstract: ContextPatients: Ninety-one of 2898 consecutive visits to a public teaching hospital emergency department were specifically for severe, uncomplicated hypertension. Results: Of 2898 consecutive medical emergency department visits, there were 142 (4.9%) patient visits specifically for systolic blood pressure (SBP) у220 mm Hg or diastolic blood pressure (DBP) у120 mm Hg. Ninety-one of the 142 patient visits were for severe hypertension in the absence of acute target organ impact or neuroretinopathy. Eighty-nine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 19 publications
0
28
1
Order By: Relevance
“…A more recent 1999 study of 74 discharged ED patients at a teaching hospital who presented with a systolic or diastolic BP of at least 220 or 110 mm Hg, respectively, found that 13.5% of participants returned to the ED within three months with significant cardiovascular complications. 18 Several studies have assessed shortterm outcomes 19,20 and found very low frequencies of poor outcomes; however, hypertension is a disease that has significant long-term, rather than short-term, impact. 3 Large studies on the long-term outcomes are needed in order to guide these management decisions and, in turn, provide consistency of care to such patients across physicians.…”
Section: Discussionmentioning
confidence: 99%
“…A more recent 1999 study of 74 discharged ED patients at a teaching hospital who presented with a systolic or diastolic BP of at least 220 or 110 mm Hg, respectively, found that 13.5% of participants returned to the ED within three months with significant cardiovascular complications. 18 Several studies have assessed shortterm outcomes 19,20 and found very low frequencies of poor outcomes; however, hypertension is a disease that has significant long-term, rather than short-term, impact. 3 Large studies on the long-term outcomes are needed in order to guide these management decisions and, in turn, provide consistency of care to such patients across physicians.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5] Considering the severe organ damage that potentially follows hypertensive crises, identification of specific patients at increased risk is important. We performed a systematic literature search including all studies evaluating predictors for hypertensive crises and found no study evaluating such predictors in a prospective design.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Whether extreme hypertension is associated with increased release of circulating EMP and PMP has not been investigated.…”
mentioning
confidence: 99%
“…evere, uncontrolled hypertension is associated with high rates of target organ complications, [1][2][3][4][5][6] but the molecular mechanisms by which extreme blood pressure elevation leads to vascular injury are not well defined. Increasing evidence suggests that hypertension confers a prothrombic state, characterized by abnormalities of endothelial function and platelet activation.…”
mentioning
confidence: 99%